THE ROLE OF VITAMIN D3 SUPPLEMENTATION ON MYASTHENIA GRAVIS COMPOSITE SCALE: A CASE REPORT - Mardhiani, Meidistya Ayu; Wina Sinaga; Diyah Eka Andayani (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2026)
Myasthenia Gravis (MG) is a rare chronic autoimmune disorder triggered by pathogenic IgG autoantibodies and complement activation. Common clinical manifestations include ocular muscle weakness, dysphagia, dysarthria, dysphonia, limb muscle weakness, generalized skeletal muscle weakness, and respiratory muscle involvement. A 47-year-old female presented with unilateral ptosis, bilateral diplopia, dysphagia, dysphonia, dysarthria, and paresis of both upper and lower extremities. The Myasthenia Gravis Composite Scale (MGCS) score was 31. Electromyography confirmed the diagnosis of myasthenia gravis, and laboratory evaluation revealed 25-hydroxyvitamin D deficiency. During hospitalization, the patient received cholinesterase inhibitors, corticosteroids, and vitamin D3 supplementation at 5,000 IU once daily for 9 days. The MGCS score decreased to 19, indicating improved functional capacity. Conclusion: Vitamin D3 supplementation at a dose of 5,000 IU/day may provide potential clinical benefits, as reflected by a reduction in MGCS score, and may also reduce the future risk of osteoporosis secondary to 25-hydroxyvitamin D deficiency. However, the clinical improvement observed in this patient was likely also influenced by the concurrent administration of cholinesterase inhibitors and corticosteroids.